Human bone marrow stromal cells: the impact of anticoagulants on stem cell properties - Ferencakova, Michaela; Benova, Andrea; Raska, Ivan; Abaffy, Pavel; Sindelka, Radek; Dzubanova, Martina; Pospisilova, Eliska; Kolostova, Katarina; Cajka, Tomas; Paclik, Ales; Zikan, Vit; Tencerova, Michaela (Frontiers in Cell and Developmental Biology, 2023)
Background: Bone marrow stromal cells (BMSCs) are the source of multipotent stem cells important for regenerative medicine and diagnostic purposes. The isolation of human BMSCs from the bone marrow (BM) cavity using BM aspiration applies the method with collection into tubes containing anticoagulants. Interaction with anticoagulants may affect BMSC characteristics and composition of isolated BMSCs in the culture. Thus, we investigated how anticoagulants in isolation procedure and cultivation affect BMSC molecular characteristics. Methods: BM donors (age:48-85 years old) were recruited from hematologic clinic. BM aspirates were obtained from iliac crest and divided into tubes coated with ethylenediaminetetraacetic acid (EDTA) or Heparin anticoagulants. Isolated BMSCs were analyzed by flow cytometry and RNA seq analysis. Further cellular and molecular characterizations of BMSCs including CFU, proliferation and differentiation assays, cytometry, seahorse, metabolomics, immunostaining, RT-qPCR were performed. Results: The paired samples of isolated BMSCs obtained from the same patient showed increased cellular yield in Heparin vs. EDTA samples, accompanied by increased number of CFU colonies. However, no significant changes in molecular characteristics were found between Heparin- and EDTA-isolated BMSCs. On the other hand, RNA seq analysis revealed increased expression of genes involved in nucleotide metabolism, cellular metabolism in cultivated vs non-cultivated BMSCs regardless of the anticoagulant, while genes involved in inflammation, chromatin remodeling were decreased in cultivated vs non-cultivated BMSCs. Conclusion: The type of anticoagulant in BMSC isolation did not have a significant impact on molecular characteristics and cellular composition, while in vitro cultivation caused the major change in the transcriptomics of BMSCs, which is important for future protocols using BMSCs in regenerative medicine and clinics.